2007
DOI: 10.2139/ssrn.1008853
|View full text |Cite
|
Sign up to set email alerts
|

Asset Pricing Implications of a New Keynesian Model

Abstract: We investigate the behavior of asset prices in a typical New Keynesian macro model. Using a second-order approximation, we examine bond and equity returns, the equity risk premium, and the behavior of the real and nominal term structure. As documented in the literature, our results suggest that introducing real rigidities to the model increases risk premia. Nevertheless we that find that, in a world dominated by productivity shocks, increasing nominal rigidities reduces risk premia. Such rigidities only enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…where for any generic variable h, ∆h t = h t − h t−1 . De Paoli et al (2010) show that the real rate can be expressed as:…”
Section: Second Order Approximations To Asset Returnsmentioning
confidence: 99%
See 2 more Smart Citations
“…where for any generic variable h, ∆h t = h t − h t−1 . De Paoli et al (2010) show that the real rate can be expressed as:…”
Section: Second Order Approximations To Asset Returnsmentioning
confidence: 99%
“…We assume that the nominal wage adjustment cost is intangible. In section 2.6 we make the same assumption for the price adjustment cost, following DePaoli et al (2010). In a separate exercise, we solved the model with tangible nominal adjustment costs and found that our results are unaffected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we extend the NK framework of Paoli et al . () by defining different term structures and rigidities and moving the analysis to an open‐economy setting. In the absence of frictions, the model exhibits the well‐known equity and term premia puzzle.…”
Section: The Modelmentioning
confidence: 99%
“…() and Paoli et al . () and model the term structure recursively. The one‐period nominal bonds deriving the standard relationship are given by dRt=πteβλtdλtφtB dRt=πteβλtdλtStdStdΦ2(.)Φ2(.)φtB where φtB is a shock to a one‐period nominal bond and λ t is the Lagrangian from the household's FOCs.…”
Section: The Modelmentioning
confidence: 99%